2016
DOI: 10.1111/ajt.13634
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Immune Effects of Myeloid-Related Proteins in Kidney Transplant Rejection

Abstract: Acute rejection is a risk factor for inferior long-term kidney transplant survival. Although T cell immunity is considered the main effector in clinical acute rejection, the role of myeloid cells is less clear. Expression of S100 calcium-binding protein A8 (S100A8) and S100A9 was evaluated in 303 biopsies before and after transplantation from 190 patients. In two independent cohorts of patients with acute rejection (n = 98 and n = 11; mostly cellular rejections), high expression of S100 calcium-binding protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 51 publications
(60 reference statements)
2
24
0
Order By: Relevance
“…Supporting this study, Rekers et al . showed that high levels of S100A8/A9 correlated with improved graft outcome after kidney transplantation . Thus, we hypothesized that S100A8/A9 would dampen macrophage‐induced inflammation and the development of renal fibrosis following UUO.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Supporting this study, Rekers et al . showed that high levels of S100A8/A9 correlated with improved graft outcome after kidney transplantation . Thus, we hypothesized that S100A8/A9 would dampen macrophage‐induced inflammation and the development of renal fibrosis following UUO.…”
Section: Discussionmentioning
confidence: 96%
“…S100A8/A9 is a critical player during inflammatory responses . Previous studies have shown that, in human diseases, S100A8/A9 can be detected in serum, aspirates or faeces of patients with rheumatoid arthritis , acute rejection , inflammatory bowel disease , lung disease , systemic sclerosis and atherosclerosis . In the context of renal fibrosis, we are the first to show that S100A8/A9 expression is increased in patients with obstructive nephropathy and localizes uniquely to interstitial granulocytes and not to other parenchymal cells, such as epithelial cells .…”
Section: Discussionmentioning
confidence: 99%
“…Expressions of human S100 calcium‐binding protein A8 and S100 calcium‐binding protein A9, which suppress immune responses, in the graft and PBMCs, are related to MDSCs marker and improved graft outcome. Rekers et al () indicated that S100 A8 and A9 proteins significantly increased during posttransplant phase versus a pretransplant period in the patients with stable graft function, but the differences were not significant in the patients with acute rejection. They also demonstrated that patients with acute rejection, expressing high levels of S100A9 mRNA, had better graft function for at least 6 years compared with patients with acute rejection, expressing decreased S100 A9 mRNA (Rekers et al, ).…”
Section: Innate Immunity In Kidney Transplantation Outcomementioning
confidence: 99%
“…The role of myeloid cells in allograft rejection has been increasingly appreciated [ 17 , 18 , 19 ]. We found in human kidney transplants that acute rejection episodes with high tissue expression of S100A8 and S100A9 have a more favorable long-term outcome than rejections with low expression [ 20 , 21 ], suggesting that the S100 proteins exert beneficial immune effects. Double immunofluorescence on tissue biopsies showed that S100A9 largely co-localized with CD68 and HLA-DR, but that only a minority of S100A9+ cells expressed the macrophage type 2 marker CD163.…”
Section: Introductionmentioning
confidence: 99%